1998
DOI: 10.1001/archotol.124.3.249
|View full text |Cite
|
Sign up to set email alerts
|

Sound- and/or Pressure-Induced Vertigo Due to Bone Dehiscence of the Superior Semicircular Canal

Abstract: We have identified patients with a syndrome of vestibular symptoms induced by sound in an ear or by changes in middle ear or intracranial pressure. These patients can also experience chronic disequilibrium. Eye movements in the plane parallel to that of the superior semicircular canal were evoked by stimuli that have the potential to cause ampullofugal or ampullopetal deflection of this canal's cupula in the presence of a dehiscence of bone overlying the canal. The existence of such deshiscences was confirmed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
792
2
47

Year Published

2000
2000
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 978 publications
(879 citation statements)
references
References 30 publications
(27 reference statements)
10
792
2
47
Order By: Relevance
“…Typical symptoms for SCDS, first described by Minor et al (1), are hyperacusis for bone conducted sounds (often autophony) and vertigo, induced by loud sounds (Tullio phenomenon) or by increased pressure in the middle ear (Hennebert sign) or in the head (e.g. during sports).…”
Section: Introductionmentioning
confidence: 99%
“…Typical symptoms for SCDS, first described by Minor et al (1), are hyperacusis for bone conducted sounds (often autophony) and vertigo, induced by loud sounds (Tullio phenomenon) or by increased pressure in the middle ear (Hennebert sign) or in the head (e.g. during sports).…”
Section: Introductionmentioning
confidence: 99%
“…Superior semicircular canal dehiscence (SCD) syndrome, first described by Minor et al (1998), is associated with sound and/or static pressure-induced vertigo. In addition to vestibular symptoms (Minor et al, 1998;Cremer et al, 2000;Minor, 2000;Brantberg et al, 2000), patients with the syndrome frequently have a super-sensitivity to bone-conducted auditory stimuli, and a decreased sensitivity to air-conducted sound (Minor et al, 2003;Mikulec et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to vestibular symptoms (Minor et al, 1998;Cremer et al, 2000;Minor, 2000;Brantberg et al, 2000), patients with the syndrome frequently have a super-sensitivity to bone-conducted auditory stimuli, and a decreased sensitivity to air-conducted sound (Minor et al, 2003;Mikulec et al, 2004). The increased air-conduction thresholds (20-60 dB) and the decreased bone-conduction thresholds (5-10 dB) together lead to a conductive hearing loss (e.g., air-bone gap) that is largest in the low frequencies (Mikulec et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1). Minor et al (1998) found that they typically suffer from sound-induced vertigo, also known as Tullio phenomenon (TP). Sound stimuli within a subrange of the audible spectrum, typically between 500 Hz and 2 kHz at sound intensities of 100-110 dB (Minor 2000), trigger vestibular reactions in the plane of the dehiscent semicircular canal.…”
Section: Introductionmentioning
confidence: 99%